Silverkin eaudiobook - Wheeler, Jeff (Tantor Media, 2018)
Buried in the catacombs beneath the fortress of Landmoor lies the Silverkin, an ancient talisman that can overcome any Forbidden Magic. Thealos Quickfellow has the right to claim the Silverkin but knows little about the deadly consequences befalling those who wield it. Before he can lay claim to it however, he must first slip beyond the web of Sorian who have beset Landmoor and battle amongst themselves for supremacy. On his journey Thealos will learn personally of the sacrifices required to become a Sleepwalker and how to use the Silverkin to save his people. But will using it destroy him?